PENGARUH NILAI CERITA ANAK DAN KESUSASTERAAN DALAM MENCIPTAKAN PENDIDIKAN HUMANIS BAGI ANAK INDONESIA - Rohmah, Galuh Nur (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2006)
Child stories and literary works have both recreative characteristics and humanity values such as personality moral, social moral and religious moral which can shape children’s ideal characteristics as a potential and strategic asset to help them to be civilized generation. The efforts to dig up the values from that two valuable sources are needed and the most possible way is through teaching the children how to appreciate child stories and literary works.